Use of electromyography to detect muscle exhaustion in finishing barrows fed ractopamine HCl - Noel, Jere Annabella; Broxterman, R. M.; McCoy, G. M.; Craig, J. C.; Phelps, K. J.; Burnett, D. D.; Vaughn, M. A.; Barstow, Thomas J.; O'Quinn, Travis G.; Woodworth, Jason C.; DeRouchey, Joel M.; Rozell, Timothy G.; et al. (My University, 2017)
The objectives of this study were to determine the effects of dietary ractopamine HCl (RAC) on muscle fiber characteristics and electromyography (EMG) measures of finishing barrow exhaustion when barrows were subjected to increased levels of activity. Barrows (n = 34; 92 +/- 2 kg initial BW) were assigned to 1 of 2 treatments: a conventional swine finishing diet containing 0 mg/kg ractopamine HCl (CON) or a diet formulated to meet the requirements of finishing barrows fed 10 mg/kg RAC (RAC+). After 32 d on feed, barrows were individually moved around a track at 0.79 m/s until subjectively exhausted. Wireless EMG sensors were affixed to the deltoideus (DT), triceps brachii lateral head (TLH), tensor fasciae latae (TFL), and semitendinosus (ST) muscles to measure median power frequency (MdPF) and root mean square (RMS) as indicators of action potential conduction velocity and muscle fiber recruitment, respectively. After harvest, samples of each muscle were collected for fiber type, succinate dehydrogenase (SDH), and capillary density analysis. Speed was not different (P = 0.82) between treatments, but RAC+ barrows reached subjective exhaustion earlier and covered less distance than CON barrows (P < 0.01). There were no treatment x muscle interactions or treatment effects for end-point MdPF values (P > 0.29). There was a treatment x muscle interaction (P = 0.04) for end-point RMS values. The RAC diet did not change end-point RMS values in the DT or TLH (P > 0.37); however, the diet tended to decrease and increase end-point RMS in the ST and TFL, respectively (P < 0.07). There were no treatment x muscle interactions for fiber type, SDH, or capillary density measures (P > 0.10). Muscles of RAC+ barrows tended to have less type I fibers and more capillaries per fiber (P < 0.07). Type I and IIA fibers of RAC+ barrows were larger (P < 0.07). Compared with all other muscles, the ST had more (P < 0.01) type IIB fibers and larger type I, IIA, and IIX fibers (P < 0.01). Type I, IIA, and IIX fibers of the ST also contained less SDH compared with the other muscles (P < 0.01). Barrows fed a RAC diet had increased time to subjective exhaustion due to loss of active muscle fibers in the ST, possibly due to fibers being larger and less oxidative in metabolism. Size increases in type I and IIA fibers with no change in oxidative capacity could also contribute to early exhaustion of RAC+ barrows. Overall, EMG technology can measure real-time muscle fiber loss to help explain subjective exhaustion in barrows.
Citation: Noel, J. A., Broxterman, R. M., McCoy, G. M., Craig, J. C., Phelps, K. J., Burnett, D. D., . . . Gonzalez, J. M. (2016). Use of electromyography to detect muscle exhaustion in finishing barrows fed ractopamine HCl. Journal of Animal Science, 94(6), 2344-2356. doi:10.2527/jas2016-0398
Keywords: Barrow; Electromyography; Exhaustion; Fiber Type; Ractopamine Hcl; Pork Quality Characteristics